The simultaneous analysis of benzene, toluene, ethylbenzene, o,m,p-xylenes and total petroleum hydrocarbons in soil by GC-FID after ultra-sonication - Shin, HS; Kwon, OS (KOREAN CHEMICAL SOC, 2000)
A simultaneous determination method of BTEX (benzene, toluene, ethylbenzene, o,m.p-xylene) and TPH (kerosene, diesel, jet fuel and bunker C) in soil with gas chromatography/flame ionization detection (GC-FID) was described. The effects of extraction method, extraction solvent, solvent volume and extraction time on the extraction performance were studied. A sonication method was simpler and more efficient than Soxhlet or shaking methods. Sonication with 10 mL of acetone/methylene chloride (1 : 1, v/v) for 10 min was found to be optimal extraction conditions for 20 g of soil. Peak shapes and quantification of BTEX and TPH were excellent, with linear calibration curves over a wide range of 1-500 mg/L for BTEX and 10-5000 mg/L fur TPH. Good reproducibilities by sonication were obtained, with the RSD values below 10%. By using about 20 g of soil, detection limits were 0.8 mg/L for BTEX and 10 mg/L for TPH. The advantages of this procedure are the use of simple and common equipment, reduced volumes of organic solvents, rapid extraction periods of less than 20 min, and simultaneous analysis of volatile and semivolatile compounds.